2011
DOI: 10.1371/journal.pone.0026576
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Risk of Co-Existing Meningitis in Children with Urinary Tract Infection

Abstract: ObjectiveThe primary aim of this study was to determine age-stratified rates of co-existing bacterial meningitis in children with urinary tract infection (UTI). The secondary aims of this study were to determine the causative pathogens of UTI, and the clinical features and outcome of children with co-existing meningitis.MethodsAnalysis of data collected over a nine-year period at a tertiary pediatric hospital in Australia. Study population: children below 16 years of age with culture-confirmed UTI and a paired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
(76 reference statements)
0
35
0
4
Order By: Relevance
“…27 More recent literature suggests that older infants (30-90 days of life) with UTI have a low rate of concurrent meningitis. [28][29][30] It has been suggested that in well-appearing infants in this age group considered to be at low risk on presentation, lumbar puncture to assess for concurrent meningitis may not be necessary. 31,32 However, because our study only examines children with bacteremia, which may indicate a higher level of illness compared with the standard child presenting with UTI, it is diffi cult to draw fi rm conclusions about the role of lumbar puncture in infants with both bacteremia and UTI.…”
Section: Discussionmentioning
confidence: 99%
“…27 More recent literature suggests that older infants (30-90 days of life) with UTI have a low rate of concurrent meningitis. [28][29][30] It has been suggested that in well-appearing infants in this age group considered to be at low risk on presentation, lumbar puncture to assess for concurrent meningitis may not be necessary. 31,32 However, because our study only examines children with bacteremia, which may indicate a higher level of illness compared with the standard child presenting with UTI, it is diffi cult to draw fi rm conclusions about the role of lumbar puncture in infants with both bacteremia and UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Enterococcus sp. in contaminated food fishes can lead to lifethreatening illness in human such as endocarditis (Dahl and Bruun, 2013), bacteremia (Stuart et al, 2006), urinary tract infection and meningitis (Tebruegge et al, 2011) and its resistance to antibiotics is emerging as a major problem in treating these infections (Koch et al, 2004). In addition, the ubiquity of Enterococcus sp in food has been reported to be mainly a result of their resistance to unfavorable environmental conditions during production technology with food fish storage conditions and their adaptability (Sarra et al, 2013).…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 136-146mentioning
confidence: 99%
“…Nonetheless, it can cause life-threatening infections such as endocarditis (1), bacteremia (2), urinary tract infection, and meningitis (3), and it appears especially in hospitals where resistance to antibiotics is developed (4). In addition, E. faecalis is frequently recovered from secondary persistent infections associated with root canal treatment failures (5,6) that can result in invasion to the tissues surrounding the tip of the tooth-root (periradicular tissue) with subsequent development of abscesses and diffused infections (cellulitis) (7).…”
mentioning
confidence: 99%